Pengaruh Brand Personality Terhadap Customer Satisfaction Menginap di the Axana Hotel Padang - Addrian Putra Pratama; Nidia Wulansari (Lembaga Pengembangan Kinerja Dosen, 2024)
This research is motivated by several problems, namely the occupancy rate at The Axana Hotel Padang is not up to target, there is hesitation for guests to stay overnight because of discomfort at The Axana Hotel Padang, the image of The Axana Hotel Padang has not been able to provide trust in guests, customer views towards the Axana Hotel Personality brand which has inadequate service, there are guest complaints regarding guest expectations not being met while staying at The Axana Hotel Padang. The research purpose is to analyze the brand personality impact on customer satisfaction. The research type used is descriptive through quantitative data. The data type used in this research is primary data. The research population were guests staying at The Axana Hotel Padang. The sample for this research are 95 guest with a sampling technique by using non-probability sampling. The technique for data collection was conducted using a questionnaire with a scale of Likert which has done process for validity and reliability test. The research data were processed by SPSS 25.00. The research results shown that brand personality is in the sufficient category, that are 3.35%. Furthermore, the customer satisfaction variable is in the sufficient category, that are 3.40%. The brand personality impact on customer satisfaction with a score in 14.6% and 85.4% is impacted by other factors. So, the multiple linear regression analysis results obtained a calculated F score is 15,947 with sig. 0.005 < 0.05, meaning that the brand personality variable has a significant effect on customer satisfaction, and the t value obtained is 3,993 with sig. 0.000 < 0.05.